Advances in Neural Signal Processing - Vinjamuri, Ramana (IntechOpen, 2020)
Neural signal processing is a specialized area of signal processing aimed at extracting information or decoding intent from neural signals recorded from the central or peripheral nervous system. This has significant applications in the areas of neuroscience and neural engineering. These applications are famously known in the area of brain-machine interfaces. This book presents recent advances in this flourishing field of neural signal processing with demonstrative applications.